Mucinous Tumors of the Ovary: Current Diagnosis in Histopathological Perspective - Florinda Ilona; Dyah Ayu Woro; Reza Aditya Digambiro (Biomedical Journal of Indonesia, 2023)
Epithelial malignant tumors account for around 90% of all ovarian malignancies and are the most deadly gynecological malignancies and mucinous borderline ovarian tumors are the most common cases in Asia. According to World Health Organization (WHO) 2020, mucinous ovarian tumors are divided into mucinous cystadenoma, borderline mucinous tumor and mucinous carcinoma. Histopathological features of benign, borderline and invasive mucinous carcinoma can be found together in one tumor. The coexixtence of these varied morphological features makes it difficult to establish a diagnosis due to the limited section evaluated and the large size of tumor. It can contribute to inaccurate diagnosis due to heterogeneity of the morphological features. Metastatic mucinous tumors which often resemble primary mucinous tumors in the ovaries.